MOTIVASI BELAJAR MAHASISWA PGSD UNDANA PADA PEMBELAJARAN DARING (STUDY FROM HOME) MENGGUNAKAN APLIKASI GOOGLE CLASSROOM DI MASA PANDEMI COVID-19 - Sarah Nurhabibah; Paulina Riwu Ga (Universitas Nusa Cendana, 2022)
This quantitative survey research aims to explain the learning motivation of PGSD UNDANA students in online learning (study from home) using the google classroom application during the Covid-19 pandemic. The research subjects were the third-semester students of class III E and III G totaling 93 people. The technique used is a survey technique with a Likert scale and a survey made and can be accessed by students via a google form. The data analysis is done by calculating the percentage of each indicator. The results showed that the percentage of learning motivation of students in the Education Study Program for Elementary School Teachers at Nusa Cendana University in online learning using the google classroom application during the Covid-19 pandemic was 92.12% with very good criteria